Social exclusion and mental well-being of older people in rural China - Tong, Hongmei; Lai, Daniel W. L.; Guo, Aimei (My University, 2016)
The growth of the aging population in China is an important reality facing professionals and policy makers working with older adults. Challenges and needs related to the mental health of older adults, particularly those in rural areas in China, have been understudied. This cross-sectional study involved 499 older adults randomly selected from four rural counties in Jiangsu Province, China. Social exclusion was measured according to material resources, housing conditions, social relations, civic participation, and basic services. Mental health indicators included depression, happiness, and worry. Hierarchical binary logistic regression analysis was conducted to examine the association between social exclusion and mental health variables. Exclusion related to material resources, housing conditions, social relations, participation, and basic community services were found to be negatively associated with mental health outcomes. Social policies and programs to reduce various forms of social exclusion should be developed in order to enhance the mental health of older Chinese in rural areas.
Keywords: psychological well-being; older people; population aging; China